(untitled) (Nigerian Journal of Technology, 2019)
Building maintenance comprises the preservation of buildings to retain their durability and economic values. It is a significant aspect of facilities management that necessitates planning. This research studied the effect of factors such as lack of maintenance policy, inadequate provision of funds for maintenance, etc, on building maintenance in the University of Ilorin. The field assessment focused on the staff residential quarters, staff offices, lecture rooms and students’ hostels. Questionnaires were administered and analysed to determine how these factors affect maintenance in the University. The results reveal that students, who are the main users of the hostels and lecture theatres believe that all the factors considered significantly contribute to maintenance failure in the University while the staff believe that change of government significantly affect maintenance in the University. It is recommended that good maintenance policies should be drawn by the University to ensure constant and regular maintenance of the infrastructures. http://dx.doi.org/10.4314/njt.v38i3.4